Presence of Bemisia tabaci (Hemiptera: Aleyrodidae) and Begomovirus, associated with tomato crops Solanum lycopersicum L. in Cundinamarca - Olga Y Martínez B; Everth E Ebratt R; Walther Turizo A; Omar Guerrero G; Rocio Acosta A (Agronomía Colombiana, 2012)
This study was undertaken to determine the presence and distribution of species of whiteflies in Cundinamarca, in the tomato, located in nine municipalities; for this purpose, insect samples were collected from the lower third of leaflets to identify nymphs of the fourth instar and from the upper third to identify adults with molecular markers RAPD-PCR (primer OPA 04); we also analyzed the presence of Begomoviruses (Family Geminiviridae) in tomato plants with nucleic acid hybridization in the nylon membrane. The results indicated the presence of Trialeurodes vaporariorum (Westwood) as the predominant species at 40.9%, Bemisia tabaci biotype B at 4.5% and coexistence at 54.6%. B. tabaci biotype B had a wide distribution with respect to other studies, between 383 to 1,857 m a.s.l. The presence of Begomovirus was related to its vector B. tabaci biotype B in 4 out of 15 tomato-producing provinces of the department. The insecticides used for control are organophosphates (41.18%), neonicotenoids (29.41%), carbamates (17.65%) and pyrethroids (11.76%). We discuss the disturbing and rapid spread of B. tabaci biotype B in Cundinamarca